(untitled) (Economic and Political Thought, 2013)
Liberals exerted considerable influence on the European integration. Both politicians associated with liberalism and liberal organizations interested in the integration of the continent had that impact. There was a feedback: various interwar ideas of uniting the continent were important for liberal programs and attempts to develop Trans-European dialogue between political parties. The article deals with international liberal movement that was involved in the European policy from the very beginning of its existence. From the late 40s Liberal International issued documents that confirmed liberals’ influence on the integration of the continent. Liberals paid attention to democratization of the Union, European institutions and citizens’ participation in the decision- -making process. The importance of liberal policy was also indicated by the participation of freedom parties in member states’ governments, in which they held key ministerial positions in spite of unstable election results.